L’audiovisuel dans les cultures wayana et apalaï : un exemple des enjeux linguistiques et identitaires en Guyane - Cécile-Marie Martin (Mise au Point)
Since the 1980s, certain indigenous communities in the Amazon have shown a growing interest in audiovisual media. Young filmmakers trained in these techniques, and assumed an important role in intercultural relations. A number of initiatives to decolonize audiovisual media have thus emerged, enabling these minority groups to make their own films as a means of establishing a dynamic and critical dialogue with the multiple representations—most of them reductive and stigmatizing—that had already been produced about them. After focusing on key issues related to the situation of one of these communities, the Wayanas and Apalaïs community, within French society, this article discusses the schemes and tools that contribute to the circulation and accessibility of media content, as well as the projects the objectives of which is to support creation, notably through media literacy initiatives.